By all necessary means? Emerging powers and the use of force in peacekeeping. Issue 3 (2nd July 2020) - Duarte Villa, Rafael; Jenne, Nicole
ABSTRACT: Emerging powers from the global south have generally opposed the use of force in international politics. However, taking a closer look at the area of peacekeeping, the international community's most institutionalized response to international insecurity, it is clear that the global south has been actively engaged in what has been described as peacekeeping's coercive turn: the increasingly greater use of force. Building on the cases of Brazil and Indonesia, we argue that the peacekeeping policies of these emerging powers have been inconsistent with their declared reticence to use force. We explain the inconsistency by reference to knowledge imbalances between civilian and military actors, a gap in peacekeeping expertise and involvement in policy-making that allowed the armed forces to push the two countries into increasingly coercive peacekeeping. Moreover, civil–military knowledge imbalances prevented the emergence of alternative ideas more in line with Brazil's and Indonesia's traditional stance on the use of force.